Global best Local Neighbourhood in Particle Swarm Optimization for Big Data Environment - Zalili, Musa; M. N. M., Kahar; Mohd Hafiz, Mohd Hassin; Rohani, Abu Bakar (Faculty of Computer System & Software Engineering, 2017)
The conventional Particle Swarm Optimization (PSO) still has weaknesses in finding optimal solutions especially in a dynamic environment. Therefore, in this paper we proposed a Global best Local Neighborhood in particle swarm optimization in order to solve the optimum solution in dynamic environment. Based on the experimental results of 50 datasets, show that GbLN-PSO has the ability to find the quality solution in dynamic environment.